2005
DOI: 10.1152/ajpregu.00369.2005
|View full text |Cite
|
Sign up to set email alerts
|

Newborn lamb coronary artery reactivity is programmed by early gestation dexamethasone before the onset of systemic hypertension

Abstract: . Newborn lamb coronary artery reactivity is programmed by early gestation dexamethasone before the onset of systemic hypertension. Am J Physiol Regul Integr Comp Physiol 289: R1169 -R1176, 2006. First published June 16, 2005 doi:10.1152/ajpregu.00369.2005.-Exposure of the early gestation ovine fetus to exogenous glucocorticoids induces organ-specific alterations in postnatal cardiovascular physiology. To determine whether early gestation corticosteroid exposure alters coronary reactivity before the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 23 publications
5
38
0
Order By: Relevance
“…[6][7][8][9][10] Human fetuses with CAH, who had received dexamethasone (DEX), had normal preand postnatal growth 11 but showed more shyness, greater emotionality, and less sociability than unexposed children. 12 Previous studies in sheep have shown that maternal intravenously DEX treatment between 26 and 28 days of gestation (dG) did not result in fetal organ weight changes at 130 dG 13 but were associated with enhanced coronary artery vascular reactivity with 4 months of age, 14 altered brain renin-angiotensin function 15 and hyperinsulinemia in response to glucose challenge at the age of 4 years. 16 Female offspring demonstrated hypertension, which was still evident at the age of 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Human fetuses with CAH, who had received dexamethasone (DEX), had normal preand postnatal growth 11 but showed more shyness, greater emotionality, and less sociability than unexposed children. 12 Previous studies in sheep have shown that maternal intravenously DEX treatment between 26 and 28 days of gestation (dG) did not result in fetal organ weight changes at 130 dG 13 but were associated with enhanced coronary artery vascular reactivity with 4 months of age, 14 altered brain renin-angiotensin function 15 and hyperinsulinemia in response to glucose challenge at the age of 4 years. 16 Female offspring demonstrated hypertension, which was still evident at the age of 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that early gestation dexamethasone (DEX) exposure, an ovine model of fetal programming with impaired coronary endothelial-mediated vasodilation [2,3] , is associated with increased coronary, mesenteric and carotid artery superoxide anion levels. We further evaluated the biologic significance of regional ROS production through evaluation of markers of oxidative injury within adjacent organs susceptible to programming insults, including the heart, liver and brain [8] .…”
mentioning
confidence: 99%
“…Sheep exposed to maternal betamethasone at 26 -28 d gestation have an elevation in blood pressure by 3 mo of age that amplifies later in adult life (2,9,26,27). In this model of fetal programming, coronary artery response to ET-1 was shown to be enhanced in 1-wk newborns and also at 5 mo of age (2,3). Repeated weekly exposure to low doses of maternally administered dexamethasone starting at 103 d of gestational age resulted in increased sensitivity to ET-1 in skeletal muscle arteries of 119 dGA fetuses, (28) with this alteration persisting postnatally up to 5 mo of age (4).…”
Section: Discussionmentioning
confidence: 86%
“…Evidence from animal models of fetal programming indicates that antenatal glucocorticoids have adverse cardiovascular effects in the adult offspring, with alterations in vascular reactivity being a common finding in animal models across several species. In sheep, antenatal exposure to dexamethasone at 27-28 dGA results in adult hypertension and alterations in mesenteric artery vascular reactivity in 123-126 dGA fetuses, and in coronary reactivity in 1-wk-old and 4-mo-old lambs (2,3). Repeated weekly exposure to low doses of dexamethasone starting at 103 dGA does not produce changes in blood pressure, but it does alter femoral artery sensitivity to ET-1 and to acetylcholine (ACh) in 5-mo-old lambs (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation